Specifity of education systems of Russia and China in the framework of global digitalization - Lyubov Nikolaevna Cherkasova; Artem Semenovich Gamparsumov (Вестник Майкопского государственного технологического университета)
The article justifies the urgency and necessity of studying the Chinese education system, education system have beencompared, strong and weak aspects of the education systems of Russia and China have been revealed. The purpose of the study is to identify the causes and analyze the intensive digitization and informatization of China, to determine the ways and means by which the Chinese education system is being modernized. The article justifies the development of distance and online learning, which covers all segments of the population and provides them with information, regardless of territorial affiliation. The aspects providing digitization of not only the production spheres, but also the educational process have been revealed. Creation of an educational space in each country becomes necessary provided that the existing communication networks that cover the whole country and determine the formation of high-quality education and a generation capable of quickly solving tasks based on information technologies. The possibilities of Chinese education to form the prerequisites for the creation of artificial intelligence have been considered, which is the fundamental task of modern humanity as a whole. The arguments for the development of educational systems in Russia and China have been presented, which have both general tendencies and differences in the implementation of programs for education digitization and informatization.